1977
DOI: 10.2307/3033531
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated Discussion of Interpretation Eliminates Actor-Observer Differences in the Attribution of Causality

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…McGuire & Millman 1965) has demonstrated that the mere expectation of persuasive attack can pro duce movement in the direction of the communication. Within the period of the present review, results consistent with a strategic view of anticipatory shifts have been obtained in experiments employing typical laboratory attitude topics , causal attributions (Wells et al 1977), judicial judgments (Saltzstein & Sandberg 1979), and personality factors (Turner 1977). Their conclusion was based on three fe atures of the effects: (a) the shifts appear to be attempts to move toward the defensible and admirable moderate positions of the attitude scale; (b) subjects "snap back" to their preexperimental positions when they no longer expect to receive the communication; and (c) shifts in the direction of the expected communication only occur when the issue is not a personally important one fo r the subjects.…”
Section: The Consistency Mo Delsupporting
confidence: 56%
“…McGuire & Millman 1965) has demonstrated that the mere expectation of persuasive attack can pro duce movement in the direction of the communication. Within the period of the present review, results consistent with a strategic view of anticipatory shifts have been obtained in experiments employing typical laboratory attitude topics , causal attributions (Wells et al 1977), judicial judgments (Saltzstein & Sandberg 1979), and personality factors (Turner 1977). Their conclusion was based on three fe atures of the effects: (a) the shifts appear to be attempts to move toward the defensible and admirable moderate positions of the attitude scale; (b) subjects "snap back" to their preexperimental positions when they no longer expect to receive the communication; and (c) shifts in the direction of the expected communication only occur when the issue is not a personally important one fo r the subjects.…”
Section: The Consistency Mo Delsupporting
confidence: 56%
“…However, in previous research which demonstrated that increased decision time has an effect on the bias, subjects were required to re-rate their attributions after a one-week delay . Also, the research which demonstrated an effect for anticipated discussion had observers expect to discuss their attributions with a researcher, presumably more expert than another subject (Wells et al, 1977). Thus, the manipulations of decision time and expected discussion in previous studies were probably more robust than those used in the current study.…”
Section: Discussionmentioning
confidence: 58%
“…Our prediction was based, in part, on consideration of some previous studies. First, a study by Wells, Petty, Harkins, Kagehiro, and Harvey (1977) demonstrated that observers who expected to discuss their attributions of an actor's behavior made less dispositionally-biased attributions for the actor's behavior than did observers who did not anticipate discussing their attributions. Second, Bierbrauer (1 979) found that observers who were asked to think about an actor's behavior for an extended period of time tended to explain the behavior in more situational terms than did observers who evaluated the actor after a short deliberation period.…”
mentioning
confidence: 99%
“…Thus any officiating decision that is potentially ambiguous is likely to be biased in the corresponding direction. Nonetheless, we conclude that the disparity in the attributions regarding the role of officials in the HFA is reflective of officials engaging in a self-serving bias (Taylor & Koivumaki, 1976;Wells, Petty, Harkins, Kagehiro, & Harvey, 1977), according to which actors deflect blame and emphasize other ''legitimate'' situational factors. This assessment, in turn, may generate in officials a measure of control and autonomy so needed in their profession because they ought to be ''neutral'' actors.…”
Section: Discussionmentioning
confidence: 84%